Boundedness of Vector-Valued Intrinsic Square Functions in Morrey Type Spaces. (30th April 2014) - Wang, Hua
Abstract : We will obtain the strong type and weak type estimates for vector-valued analogues of intrinsic square functions in the weighted Morrey spacesL p, κ ( w ) when1 ≤ p < ∞, 0 < κ < 1, and in the generalized Morrey spacesL p, Φ for1 ≤ p < ∞, whereΦ is a growth function on( 0, ∞ ) satisfying the doubling condition.